Freshwater aquatic reptiles (Testudines and Crocodylia) as biomonitor models in assessing environmental contamination by inorganic elements and the main analytical techniques used: a review - dos Santos, Rayssa Lima; de Sousa Correia, Jozelia Maria; dos Santos, Ednilza Maranhão (Environmental monitoring and assessment, 2021)
Despite the general lack of studies that use reptiles as bioindicators, the value of freshwater turtles and crocodilians in ecotoxicology has been proven, due to their importance as sentinel species. The aim of this study was to compile information on the use of freshwater turtles and crocodilians as environmental biomonitors of inorganic element contamination. We searched for articles in databases using specific keywords. A total of 104 studies published between the years 1970 and 2020 were collected. We noted a general increase in the number of studies involving turtles and crocodilians during the study time period. The Order Testudines were the subjects of 46% of the analysed publications, and the Order Crocodylia accounted for 54%. Within these studies, we counted 39 species (turtles n = 29 and crocodilians n = 10). Forty chemical elements were evaluated in the analysed articles, of which the majority represented non-essential elements (Hg, Cd, Pb). Although internal organs constituted the main biological matrix chosen for each group (37%), we observed an increase in the use of non-destructive matrices in both groups (scale, blood, tail muscle, carapace). The majority of analysed studies used HNO 3 for the sample decomposition, with the majority of analyses being performed using atomic absorption spectroscopy (53%). Mainly blank controls (19%), analyte recovery (18%) and replicates (18%) were used as methods of validating analytical procedures. Furthermore, the studies used certified reference materials, which measure the accuracy of the methods used. We conclude that the increase in the use of aquatic reptiles in environmental monitoring research is mainly due to their ability to reveal integrated changes in ecosystems, aiding in environmental public policy decision-making and effective management plans.